MEDICINAL VALUE OF LAGERSTROEMIA SPECIOSA: AN UPDATED REVIEW - AL-SNAFI, ALI ESMAIL (International Journal of Current Pharmaceutical Research, 2019)
Lagerstroemia speciosa (Family: Lythraceae) is native to Asia-tropical and subtropical regions. The phytochemical investigation of Lagerstroemia speciosa leaf and fruit revealed that it contained steroids, terpenoids, glycosides, phenolic compounds, α-amino acids, saponins, starch, alkaloids, carbohydrates, organic acids, flavonoids, reducing sugars, tannins and many other active metabolites. Lagerstroemia speciosa possessed many Pharmacological effects included antimicrobial, antioxidant, anticancer, antidiabetic, hypolipidemic, antiobesity, anti-inflammatory, analgesic, gastrointestinal, diuretic, thrombolytic, cardiovascular, central nervous, inhibition of TNFα production, xanthine oxidase inhibitition, hepatoprotective and nephroprotective effects. The current review discussed the chemical constituents, pharmacological and therapeutic effects of Lagerstroemia speciosa.